UPAYA MENINGKATKAN HASIL BELAJAR IPAS PESERTA DIDIK KELAS IV SD N BANJARSARI 5 MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - Ahmad Dikri; Rina Yuliana; Sri Hayati (Journal of Professional Elementary Education, 2023)
Learning outcomes are the final part of a learning process that is carried out and is a benchmark for the success of a lesson. The acquisition of student learning outcomes is influenced by the learning process given by the teacher to students. Therefore the learning process becomes something that needs to be considered in achieving optimal learning outcomes for students. The cooperative learning model of the Student Team Achievement Division (STAD) type is one of the solutions in improving the learning process so that it can improve student learning outcomes. This research is a classroom action research (CAR) to improve student learning outcomes. This research was conducted in class IV science learning at SD N Banjarsari 5. The results showed that there was an increase in learning outcomes by applying the Student Team Achievement Division (STAD) cooperative learning model in class IV students, namely, in the pre-cycle phase, the classical mastery power was 42.42%, then in the first cycle there was an increase of 64.64% after implementing the Student Team Achievement Division (STAD) cooperative model. Then in cycle II, there was an increase in student learning outcomes that was equal to 87.88% and had achieved the predetermined mastery indicators